14C Activity in Different Sections and Chemical Fractions of Oak Tree Rings, AD 1938–1981. Issue 3 (18th July 2016) - Olsson, Ingrid U.; Possnert, Göran
Abstract : The 14 C activity in rings from an oak tree grown in a suburb of Uppsala, Sweden has been studied for the period, AD 1938 to 1981. We compare the results with the atmospheric carbon dioxide records from Abisko, northern Sweden, where local or regional contamination from fossil-fuel combustion can be disregarded. We assess the influence from different chemical pretreatment procedures in use and compare HCl-NaOH-HCl treatment with cellulose extraction. We split each ring into two samples corresponding to early (spring) and late wood. A more refined partitioning has been applied to the years 1963 and 1964.